PERAN KEPALA SEKOLAH SEBAGAI EDUPRENEUR UNTUK TRANSFORMASI SEKOLAH YANG UNGGUL DI MTS NEGERI 1 CILACAP - Tuti Alawiyah Azzahra; Muh. Hanif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The principal's leadership is one of the effective forces in school management, school survival, especially in terms of development efforts, the progress of the entire school and is responsible for addressing changes in the world of education. The purpose of this study is to determine how the principal manages learning and continuous improvement in schools, and how the principal's leadership style and strategy affect the school's ability to adapt and transform in responding to changes in the educational environment. Qualitative research methods through interviews, observations, and documentation. The results of the study, the principal as an edupreneur uses a transformational and democratic leadership style by developing superior programs and providing special training to be able to compete to become a superior school.